Pengaruh Advertising, Sales Promotion, Personal Selling dan Publicity terhadap Minat Nasabah dalam Mengajukan Pembiayaan KPR di BTN KCS Bandung - Nelly Nurfitriani Utari; Ida Rapida (Jurnal Dimamu, 2023)
Based on observations, that the background of this research is the lack of incessant promotion of advertising, sales promotion, personal selling and publicity, the amount of competition between banks, both conventional banks and Islamic banks that affect the decline in the number of customers. The object of research in this report is mortgage financing customers at BTN KCS Bandung. The type of research is quantitative associative with the type of data and uses data collection techniques in the form of observation, interviews, literature studies, questionnaires. While the sampling technique is non-probability sampling with purposive sampling. The population is all customers who apply for mortgage financing at BTN KCS Bandung in 2021, totaling 1316 customers with a sample of 93 customers. The results showed that the advertising variable partially affected 53.4% ??of customer, the sales promotion variable partially affected 36.2 % of customer, the personal selling variable partially affects 22.2% of customer, the publicity variable partially affects 37.1% of customer, and simultaneously advertising, sales promotion, personal selling and publicity have an effect of 59.3% on the interest of confidence in applying for mortgage financing at BTN KCS Bandung.